Management of anthracnose disease (Colletotrichum gloeosporioides (Penz) Penz & Sac.) of black pepper (Piper nigrum L.) in the high ranges of Idukki District, Kerala - M Murugan, K N Shiva, P Sainamole Kurian, G Sivakumar, A Josephrajkumar, S Backiyarani (Journal of Spices and Aromatic Crops, 2008)
Evaluation of contact and systemic fungicides for the management of anthracnose disease(caused by Colletotrichum gloeosporioides) on black pepper (Piper nigrum) at Idukki District (Kerala)indicated that the incidence of the disease on leaves and spikes was significantly lower invines treated with a combination fungicide containing carbendazim + mancozeb 0.1% followedby carbendazim 0.1%. The dry berry yield was also significantly highest (742.7 g vine-1) invines treated with carbendazim + mancozeb 0.1%.